Cultural friction during intercultural service encounters with Chinese tourists: perspectives from hotel employees in Australia - Wen Hao Liang (Cogent Social Sciences, 2024)
This study aims to investigate the experiences and outcomes of intercultural service encounters between hotel employees and customers, including the underlying factors attributed to these outcomes. A qualitative research approach using the critical incident technique was adopted by conducting 20 semi-structured interviews with hotel employees who frequently engaged in intercultural service encounters with Chinese tourists. The findings revealed that critical incidents were mainly attributed to cultural differences in language, customs, and preferences. These cultural differences with Chinese guests can lead to outcomes such as service failures, which can be a stressor for hotel employees in Australia and trigger emotions such as frustration and intimidation. The study found that non-cultural factors such as the characteristics of customers and service employees can impact the outcome of an intercultural service encounter. This study contributes to intercultural service encounters literature by offering a new perspective from service providers’ viewpoint on their intercultural interactions. It is imperative for hotels to comprehend and work through these cultural differences to succeed in the global hospitality market. Moreover, this study offers important practical implications for hotels regarding how to best facilitate intercultural service encounters to ensure positive outcomes for both customers and service employees.